Analisis forcasting produksi dan hasil seleksi (Permak) Sarung Tangan PT. Adi Satria Abadi (ASA) Desa Sidokerto,Rt.03 / Rw. 01 Purwomartani, Kalasan Sleman Yogyakarta 55571 - Nanang Permana (Fak. Saintek UIN Sunan Kalijaga, 2013)
ng/rt